Use of a dual-layer amniotic membrane in the treatment of diabetic foot ulcers: an observational study. (1st September 2020) - Sledge, Isabella; Maislin, David; Bernarducci, Dave; Snyder, Robert; Serena, Thomas E
Abstract : Background: Despite advances in the treatment, fewer than half of diabetic foot ulcers (DFUs) heal in 12 weeks and 85% of non-traumatic amputations follow the development of a DFU. The search for treatment options continues. Placental-derived products have shown promise in the treatment of DFUs. This study investigates Artacent (Tides Medical, US), a unique amniotic patch containing two layers of amnion and its potential to increase growth factor delivery. Method: This observational analysis included patients with DFUs with documented failure to heal by >50% after the protocol-defined run-in period (either two or four weeks) of standard of care (SOC), and who had been randomised in a larger clinical trial that had been discontinued earlier for logistical reasons. Patients were randomised to either weekly or biweekly application of the dual-layer amniotic membrane (DLAM) plus SOC and were included in per-protocol effectiveness analyses. Descriptive statistics were chosen for this analysis. Primary endpoint was complete closure at 12 weeks. Results: A total of 26 patients were included in the analysis. Examination of baseline patient characteristics revealed that the ulcers were larger than in most DFU clinical trials (4.65±4.89cm 2 ). For the primary endpoint, 17/26 (65%, 95% CI: 44–83%) of the combined treatment arms achieved complete closure. The small sample size precluded a meaningful comparison of healing between weekly and biweekly DLAM applications. Conclusion: The observations taken from the discontinued clinical trial suggest that the DLAM promotes healing of DFUs. The healing rates are similar to those in other placental-based tissue studies. In addition, the relatively larger size of the ulcers suggests that the DLAM may be effective in ulcers that are more resistant to standard of care. In the future, a revised clinical trial with a greater sample size is planned.